CSR best practices for global multi‐tier sustainable supply chain integration of Chinese MNEs. (6th June 2022) - Scuotto, Veronica; Chin, Tachia; Pezzi, Alberto; Pironti, Marco
Abstract: The interest in global multi‐tier sustainable supply chains is growing proportionally to its increase in developing countries. Developing countries are considered the new fertile territory for developing global chains for multinational enterprises (MNEs). Despite the positive outcomes derived from this global development, it also induces negative impacts in the domain of domestic firms' competition, education, welfare and infrastructure system. A way to overcome this pessimistic view has been found in corporate social responsibility (CSR) best practices. MNEs seek to involve local stakeholders in their social activities to show their commitment and generate innovations. It calls for a multi‐tier domestic involvement integrated into a global supply chain to create value. This study builds its empirical analysis exploring a range of 1547 Chinese manufacturing multinational enterprises listed in the Shanghai and Shenzhen stock exchanges between 2010 and 2018. The findings revealed that multi‐tier supply chain integration (SCI) practices positively moderate the relationship between CSR and MNE performance. In turn, it implies benefits for developing sustainable development goals, generating new job opportunities mostly in the developing countries guaranteeing wealth employment conditions. The sense of involvement and engagement towards their employees requires more development of CSR practices, which can be moderated by multi‐tier SCI, as shown in the present study.